METAMORPHIC ANALYSIS IN SONG LYRICS BATAK TOBA “JUJUNG GOARHI AMANG” (STUDY OF PORTRAY OF PARENTS) - Marudut Bernadtua Simanjuntak; Zuriyati Zuriyati; Ninuk Lustyantie (IKIP Siliwangi, 2022)
This study aims to analyze the metamorphic sentences contained in popular folk songs in Indonesia.